In situ characterization of thermo-responsive poly(N-Isopropylacrylamide) films with sum-frequency generation spectroscopy - Kurz, Volker L.; Grunze, Michael; Kölsch, Patrick (ChemPhysChem, 2010)
The thermo-responsive behaviour of thiol modified poly(N-isopropylacrylamide) (pNIPAM) films immobilized on gold are probed by in situ broadband sum-frequency generation (SFG) spectroscopy. The pNIPAM films were prepared by atom transfer radical polymerization (ATRP) using a nitro-biphenyl-thiol (NBT)-SAM on a polycrystalline gold surface as a substrate. Additionally, Raman and infrared reflection absorption spectroscopy (IRRAS) are applied to spin-coated pNIPAM films. Molecular groups involved in the reorientation and disordering of the polymer chains during the LCST (lower critical solution temperature) transition of pNIPAM are identified. The characteristic vibrations of the CH3 groups show a gradual reorientation of the isopropyl groups within the pNIPAM film and instantaneous reorientation of the outermost CH3 groups around 32 °C.